Assessment of the mandibular incisive canal by panoramic radiograph and cone-beam computed tomography - Dilek Menzġletoğlu (Selçuk University, 2017)
Background: This study aimed to evaluate the location and characteristics of mental foramen, anterior loop and mandibular incisive canal using cone beam computed tomography (CBCT) and digital panoramic radiograph (DPR).Methods: 430 patients both DPRs and CBCTs scans for the location of mental foramen, anterior loop and mandibular incisive canal visibility were included in this retrospective study. All CBCTs were generated with a cone-beam volumetric tomography device.Results: The mandibular incisive canal (MIC) at least one side in the interforaminal region was detected in 17.7% of panoramic images and 89.1% of CBCT images. There was statistically significant difference between two methods (p=.000) in terms of MICs detection.Conclusion: When planning a surgical operation between the mental foraminas, possibility of the presence of MIC should be taken into consideration. Besides, DPR is not a reliable technique in detecting MIC. In critical situations, use of CBCT is recommended.